Técnicas auxiliares para a otimização da performance do oboísta com restrições musculoesqueléticas geradas pela artrite reumatoide - Rojas, Sandra Paola Romero (2024)
The quality and longevity of an instrumentalist's career are closely linked to their health. As musicians strive to improve their technical and artistic skills, they often face pressures that can affect their physical, mental, and emotional stability and integrity. Among the injuries that directly impact the performance of instrumentalists is rheumatoid arthritis (RA), a chronic inflammatory disease that affects the joints, causing pain, swelling, and stiffness. These physical limitations result in restricted joint mobility and loss of muscle strength, compromising musical performance and raising uncertainties about the individual's ability to continue their professional activities as an instrumentalist. This work presents an autoethnographic case study of my personal experience with the musculoskeletal limitations caused by rheumatoid arthritis (RA), which reshaped my perspective as a musician. The aim of this research was to systematize the practice of auxiliary techniques and technical-interpretive exercises focused on the oboist's health, in order to prevent and manage the musculoskeletal restrictions caused by RA that affect my musical performance. The literature review gathered information on prevalent musculoskeletal limitations in musicians and therapeutic exercises used to treat RA injuries, particularly in the upper limbs. Based on this information, experimentation and evaluation of selected exercises were conducted, serving as parameters for maintaining hand and finger mobility, as well as adapting technical-interpretive exercises applied to oboe performance. The systematization of these practices, combined with body awareness techniques, enabled me to resume my role as an instrumentalist, allowing for consistently effective performances. In this process of re-signifying my role as a performer, it was essential to recognize the role that emotional and psychological states play in musical performance. Anxiety, frustration, and stress, which are common in periods of intense musical dedication, can directly influence performance, exacerbating physical limitations that impact musical expression. Thus, there is a need to develop and implement practices focused on the health and well-being of instrumentalists, promoting a more holistic view of musical performance. The balance of physical, emotional, and mental aspects is essential for full artistic development, enabling the sustainable enhancement of technical and interpretative skills, while promoting the musician's overall health.